CD137 Agonists Targeting CD137-Mediated Negative Regulation Show Enhanced Antitumor Efficacy in Lung Cancer - Yi, Ling; Jin, Xin; Wang, Jinghui; Yan, Zhuohong; Cheng, Xu; Wen, Tao; Yang, Bin; Wang, Xiaojue; Che, Nanying; Liu, Zhidong; Zhang, Hongtao (Frontiers in Immunology, 2022)
Negative immune regulation plays a notable role in tumor immunity. This study aimed to confirm that CD137 mediates negative immunoregulation as well as agonist activity in tumor immunity. Soluble CD137 (sCD137), a prominent splice variant of membrane-bound CD137 (mCD137), was identified, and its concentration in the blood of lung cancer patients was increased. The baseline concentration of sCD137 in the blood was negatively correlated with the efficacy of neoadjuvant immunochemotherapy in a pilot study. The percentage of CD137+ regulatory T cells (Tregs) in the blood of lung cancer patients was also increased, and further enriched at the tumor site; Foxp3, CTLA-4, IL-10, IL-35-Ebi3, sCD137 and costimulatory molecules expression were also higher, indicating increased immunosuppressive activity. A high percentage of CD137+ Tregs in the tumor was associated with worse OS outcomes among patients with high CD137+CD8+ T cell infiltration levels. Notably, targeting CD137+ Tregs using an engineered CD137 agonist with wild-type mouse IgG2a Fc clearly decreased the total Treg numbers and eliminated the tumor in the CT26 model and prolonged the survival rate of a Lewis lung carcinoma (LLC) model. These results indicated it may be possible to empower CD137 agonist with ability to abolish CD137-mediated negative regulation to enhance its antitumor efficacy.